2007
DOI: 10.1007/s11746-007-1037-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oleic Acid Content in the Soybean Mutant M23 Is Associated with the Deletion in the Fad2‐1a Gene Encoding a Fatty Acid Desaturase

Abstract: Oleic acid is one of the three major unsaturated fatty acids in soybean oil. Expression of the embryo-specific Fad2-1 gene correlates with fatty acid biosynthesis and oil deposition in developing seeds. Elevated levels of oleate in the X-ray-induced mutant line M23 have been shown to be associated with the deletion of a Fad2-1 gene. In soybean, two homologs of the Fad2-1 gene, termed Fad2-1a (L43920) and Fad2-1b (AY611472), presumably encode functional embryo-specific fatty acid desaturase. The objectives of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Several soybean cultivars with increased oleate content are available, one of which is the midoleate mutant line M23 (Rahman et al, 1994) derived from x-ray mutagenized seed of the Bay soybean cultivar. Genetic studies indicated that the midoleate pheno- type of M23 is associated with the deletion of FAD2-1A (Alt et al, 2005;Sandhu et al, 2007;Anai et al, 2008). Given the agronomic importance of M23 in current breeding programs (Scherder et al, 2008) for increased seed oleate content, CGH could also be utilized to define the presence of other genetic lesions in the M23 genome, in addition to the previously reported FAD2-1A deletion.…”
Section: Fn Mutants With Visual Phenotypesmentioning
confidence: 99%
“…Several soybean cultivars with increased oleate content are available, one of which is the midoleate mutant line M23 (Rahman et al, 1994) derived from x-ray mutagenized seed of the Bay soybean cultivar. Genetic studies indicated that the midoleate pheno- type of M23 is associated with the deletion of FAD2-1A (Alt et al, 2005;Sandhu et al, 2007;Anai et al, 2008). Given the agronomic importance of M23 in current breeding programs (Scherder et al, 2008) for increased seed oleate content, CGH could also be utilized to define the presence of other genetic lesions in the M23 genome, in addition to the previously reported FAD2-1A deletion.…”
Section: Fn Mutants With Visual Phenotypesmentioning
confidence: 99%
“…The two mutant FAD2-1 alleles (FAD2-1A S117N and FAD2-1B P137R) as well as mutant FAD3A and FAD3C were segregating in this population. The mutant FAD2-1B, FAD3A and FAD3C genes used in this research are identical, while two mutant FAD2-1A alleles were evaluated: the FAD2-1A alleles donated from either M23 (D) or 17D (S117N) (Dierking and Bilyeu 2009;Pham et al 2010;Sandhu et al 2007).…”
Section: Population Developmentmentioning
confidence: 99%
“…Naming convention: the combination of four mutant genes: FAD2-1A, FAD2-1B, FAD3A and FAD3C herein is represented as either HO(D)LL4ac or HO(S117N)LL4ac, to distinguish the null FAD2-1A allele donated from either M23 (D) or 17D (S117N) (Dierking and Bilyeu 2009;Sandhu et al 2007). The three mutant gene combination of FAD2-1A, FAD2-1B and FAD3A is designated as HO(D or S117N) LL3a, while the three mutant gene combination of FAD2-1A, FAD2-1B and FAD3C is designated as HO(D or S117N)LL3c.…”
Section: Population Developmentmentioning
confidence: 99%
“…The FAD2-2A gene was closely linked to the FAD2-2B gene on Gm19 (LG-L) (Schlueter et al 2007). The deletion of FAD2-1A was associated with the increased oleic acid content in the mutant line M23 (Sandhu et al 2007). A minor oleate QTL was detected in the proximity of the FAD2-2B gene on Gm19 (LG-L) (Bachlava et al 2008).…”
Section: Introductionmentioning
confidence: 91%